2001
DOI: 10.1016/s0896-6273(01)00543-8
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Mediates Rapid Recruitment of Fast-Releasing Synaptic Vesicles at a Calyx-Type Synapse

Abstract: In many synapses, depletion and recruitment of releasable synaptic vesicles contribute to use-dependent synaptic depression and recovery. Recently it has been shown that high-frequency presynaptic stimulation enhances recovery from depression, which may be mediated by Ca2+. We addressed this issue by measuring quantal release rates at the calyx of Held synapse and found that transmission is mediated by a heterogeneous population of vesicles, with one subset releasing rapidly and recovering slowly and another o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
491
5
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 337 publications
(545 citation statements)
references
References 78 publications
47
491
5
2
Order By: Relevance
“…Although the CaM-binding sites of myosin-Va and CaMKII are distinct (Bähler and Rhoads, 2002), their Ca 2ϩ -dependencies for syntaxin-1A binding are very similar. Our current studies also could explain the involvement of CaM in exocytosis (Sakaba and Neher, 2001) and other CaM-dependent interactions (Junge et al, 2004).…”
Section: Cam-dependent Regulation Of Exocytosis Through Ca 2؉ -Dependmentioning
confidence: 52%
“…Although the CaM-binding sites of myosin-Va and CaMKII are distinct (Bähler and Rhoads, 2002), their Ca 2ϩ -dependencies for syntaxin-1A binding are very similar. Our current studies also could explain the involvement of CaM in exocytosis (Sakaba and Neher, 2001) and other CaM-dependent interactions (Junge et al, 2004).…”
Section: Cam-dependent Regulation Of Exocytosis Through Ca 2؉ -Dependmentioning
confidence: 52%
“…Calmodulin also mediates rapid recruitment of fast-releasing synaptic vesicles at the calyx of Held 97,98 , further underlining the intimate connection between presynaptic Ca 2+ , release site clearance and endocytosis. other Ca 2+ -binding proteins, such as calcineurin 87,88,99,100 , synaptotagmins, complexins or Munc13 (REFS 12,101) might be additional Ca 2+ effectors facilitating exocytic-endocytic coupling.…”
Section: Calcium Regulationmentioning
confidence: 96%
“…The sustained phase of release late during the presynaptic depolarization was presumably attributable to the recruitment of synaptic vesicles. It has been shown that the recruitment of synaptic vesicles has a time constant of 100 -300 ms (Wu and Borst, 1999;Sakaba and Neher, 2001b). When the effect of recruitment was corrected , the slow component saturated earlier during the depolarizing pulse (Fig.…”
Section: Synchronous and Asynchronous Release During A 100 Hz Train Omentioning
confidence: 96%
“…Two sets of readily releasable vesicles (termed fast-releasing and slowly releasing vesicles here) can be distinguished that are distinct with respect to their release probability and speed of recruitment (Wu and Borst, 1999;Sakaba and Neher, 2001b). This study addresses how fast-releasing and slowly releasing vesicles are used during a high-frequency train of AP-like stimuli.…”
Section: Introductionmentioning
confidence: 99%